PELAKSANAAN ASESMEN DALAM PERKEMBNGAN MOTORIK HALUS DI TK PUTRA 1 PALEMBANG - Oktamarina, Lidia; Khasanah, Wahidatul; Amanda, Yosi; Afrianti, Alvika Dwi; Amaliah, Amaliah (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2023)
The purpose of this research is to find out the material activities in developing children's physical motor (fine), describe the application of assessment techniques, and the results of the impact of the assessment of physical motor development (fine) at Putra 1 Kindergarten. The data sources in the study are divided into two categories, namely human and non-human categories. The human category data source is the Putra 1 Kindergarten class teacher, while the non-human data is the result of the child's assessment. Data collection techniques carried out by researchers, namely semi-structured interviews recorded and documented in the form of fine motor development assessments conducted which were carried out for three days, namely Monday, Tuesday, Wednesday. Regarding checking the validity of the research results, the researcher used an interview technique with one of the teaching teachers. The results of this research show that the activity material in developing children's fine motor skills is in the form of drawing, coloring, cutting. The assessment techniques used are observation, checklist, and work. Assessment has a positive impact on the achievement of physical motor development (fine), both for teachers, students, and parents